Analysis of Public Administration Experience Providing Emergency Medical Care in the Republic of Poland, the Possibility to Use it in Ukraine - Korol`, Andriy (Pressing Problems of Public Administration, 2019)
The purpose of the article is to summarize the experience of the Republic of Poland in the organization and public administration of the system of providing emergency medical care and the possibility of adapting this experience in Ukraine. According to an organizational criteria, the provision of emergency medical care in the Republic of Poland is the responsibility of the state, that means, it is the state administration responsibility to ensure this process, and it is  nanced by the state budget. The main principles in the process of public administration of the provision of the emergency medical care process are human-centeredness, humanity, and timeliness. The Polish experience in organizing training of people who are obliged to provide emergency medical care to the citizens is analyzed. Analyzing the training of medical staff in higher educational institutions of the Republic of Poland, we can distinguish those provisions that are appropriate to be implemented in Ukraine. In particular, it is an autonomous activity of higher educational institutions (educational-scienti c,  nancial-economic, personnel). The main directions of such autonomy, in our opinion, should be as follows: - the students enrollment according to the criteria of higher educational institutions; - the content of the training programs should be put on the responsibility of high educational institutions , followed by the passing of the independent Uni ed State Quali cation Exam. Based on the analysis, the main components of the emergency medical care system in Poland are identi ed. The main directions of ensuring the legal mechanism of the emergency medical care provision system public administration in Poland are determined. The modern approaches to training for emergency medical care are summarized. The possibility of using Polish experience in organization and public administration of emergency medical care system for its adaptation and implementation in Ukraine is determined.